Web based cache and virtual memory simulator - Chua, Yi Xiang (Nanyang Technological University, 2024)
This study presents the iterative development of an educational simulator for cache and virtual memory. The previous iteration of the simulator, which was entirely frontend-based, limited the educators’ ability to collect data on student engagement and comprehension. Recognising the potential for better educational insights, the system architecture was expanded by integrating a backend server built using the Express.js framework and a NoSQL database management system, MongoDB, transforming the simulator into a full-stack web application. This opens up possibilities for collecting, storing, and analyzing user interaction data, giving instructors valuable insights into their students’ performance and areas of difficulty. To further aid in this, data visualisation for a variety of metrics was implemented, both aggregate data as well as individual metrics, providing the big picture and the granular details when needed. These changes enable educators to efficiently plan their course curriculum to address difficult areas students may struggle in. The design of the database schema, RESTful API, and others were carefully considered and explained. Postman was utilised as an essential testing tool for ensuring that API responses between the client and backend server remain correct.